Solving linear two-dimensional Fredholm integral equations system by triangular functions - Hengamian Asl, Elias; Nadjafi, Jafar (International Journal of Applied Mathematical Research, 2016)
In this paper, we intend to offer a numerical method to solve linear two-dimensional Fredholm integral equations system of the second kind. This method converts the given two-dimensional Fredholm integral equations system into a linear system of algebraic equations by using twodimensional triangular functions. Moreover, we prove the convergence of the method. Finally the proposed method is illustrated by two examples and also results are compared with the exact solution by using computer simulations.